Ideology and Discourse Strategies in Selected Radio News of Osun State Broadcasting Corporation, Nigeria (2012)
Previous studies on news in electronic media in Nigeria have mostly concentrated on linguistic and stylistic features with little attention on discourse strategies and underlying ideological factors considered to be significant in the construction and full understanding of radio news. There is need for more attention to be paid to ideologies and discourse strategies in media discourse as they enhance the comprehension of radio news. This study, therefore, investigated the discourse strategies and political ideologies in selected radio news of Osun State Broadcasting Corporation, (OSBC), with a view to revealing the interaction between the strategies and ideologies. The OSBC was selected for its unique engagements with political ideologies. The study was carried out within the framework of Critical Discourse Analysis (CDA) which links the text with underlying power relations and ideologies, using Wodak‟s sociohistorical and van Dijk‟s socio-cognitive models. These are complemented with Halliday‟s Systemic Functional Grammar (SFG) for its emphasis on the form/function relationship in language use. A total of 1000 written news reports from the OSBC were collected between April 2007 and November 2010, out of which 250 (25%) were purposively sampled, based on their political contents. The period was selected because of the political tension that characterized the election situation in the State during the regime of Governor Olagunsoye Oyinlola. A content analysis of the news was carried out using the tools of SFG and CDA. Three major political ideologies namely, historicist, humanitarian, and welfarist, were observed to influence the deployment of specific discourse strategies in the construction of political news in the OSBC radio during the regime of Governor Olagunsoye Oyinlola. Government was projected as welfarist and humanitarian in its political agenda. Historicist ideology was characterised by the use of temporality and historical comparison of events. The linguistic tool of lexicalisation was used to foreground the humanitarian and welfarist ideologies of the government. The historicist ideology was characterised by the use of transitive clauses with a high degree of transitivity which comprised spatio-temporal adverbials and verbal choices for detailed material, mental and relational processes representing the actions and activities of prominent political actors in the news events. For humanitarian and welfarist ideologies, the strategies utilised were blame transfer, source avoidance, positive self-presentation and negative other-presentation, foregrounding of figures and statistics, manipulation, and authoritarianism. Blame transfer exonerated the political actors from the ills of the society and shifted the blame on the opponents. Events that portrayed the ruling political party positively and the opposition negatively were emphasized and given prominence while those that portrayed the ruling party negatively and the opponents positively were defocussed. There is a close interaction between political ideology and the discourse strategies used to project it in OSBC radio news texts. This interaction throws useful insights into the ideational process that is crucial in the construction of radio news. Future studies should undertake an analysis of the link between ideology and television news.